Inorganic pyrophosphate plasma levels in patients with GGCX-associated PXE-like phenotypes - Li, Qiaoli; Troutman, Catherine; Peckiconis, Mary; Wurst, Tamara; Terry, Sharon F. (Frontiers in Genetics, 2024)
Pseudoxanthoma elasticum (PXE) is an autosomal recessive ectopic calcification disorder clinically affecting the skin, eyes, and vascular system. Most cases of PXE are caused by inactivating mutations pathogenic variants in the ABCC6 gene encoding a hepatic transmembrane efflux transporter, which facilitates the extracellular release of ATP, the precursor of inorganic pyrophosphate (PPi), a potent endogenous inhibitor of calcification.Mutations Pathogenic variants in GGCX, encoding γ-glutamyl carboxylase required for activation of vitamin K-dependent coagulation factors as well as matrix Gla protein (MGP) and Gla-rich protein (GRP), two inhibitors of ectopic calcification, have also been reported to cause cutaneous changes like those seen in PXE. While ectopic calcification in ABCC6 deficiency has been associated with reduced plasma levels of PPi due to loss of ABCC6 transport activity in the liver, plasma PPi levels have not been reported in patients with GGCX-associated phenotypes.Here, we report five patients from three unrelated families' clinical, laboratory, and molecular evaluations who carry biallelic variants in GGCX and present with phenotypic characteristics associated with PXE. The variants were identified using a next-generation sequencing panel consisting of 29 genes associated with ectopic calcification. This study demonstrates that in addition to ABCC6, GGCX variants can cause the PXE phenotype, expanding PXE and perhaps other heritable ectopic calcification disorders' clinical and genetic heterogeneity. The results also show that the plasma concentrations of PPi in these patients are not reduced compared to healthy control individuals, suggesting that plasma PPi does not govern ectopic calcification in GGCX deficiency.